East of the Line (Symphony in the Flint Hills, 2017)
Introduction: In 1867 the only thing standing between the prized stock of westward-marching settlers and droves of disease-carrying longhorns was an imaginary straight line. The Sixth Principal Meridian was the boundary between east and west, settled and unsettled, tallgrass and shortgrass.
Keywords: introduction; Chisholm Trail; shortgrass prairie; tallgrass prairie